'It's Kinda Punishment': Tandem Logics and Penultimate Power in the Penal Voluntary Sector for Canadian Youth. Issue 3 (4th September 2019) - SALOLE, ABIGAIL
Abstract: This article draws on original empirical research in Ontario, Canada which analyses penal voluntary sector practice with youth in conflict with the law. I illustrate how youth penal voluntary sector (YPVS) practice operates alongside, or in tandem with the statutory criminal justice system. I argue that examining the penal voluntary sector and the statutory criminal justice system simultaneously, or in tandem, provides fuller understandings of penal voluntary sector inclusionary (and exclusionary) control practices (Tomczak and Thompson 2019). I introduce the concept of penultimate power, which demonstrates the ability of penal voluntary sector workers to trigger criminal justice system response towards a young person in conflict with the law. My novel concepts of tandem logics and penultimate power are useful for understanding penal voluntary sector practice, explaining how seemingly contradictory approaches across state and 'community' organisations not only coexist, but depend upon the tandem relationship between the penal voluntary sector and the statutory criminal justice system.